The use of weighted health‐related Quality of Life scores in people with diabetic macular oedema at baseline in a randomized clinical trial. Issue 1 (13th October 2014) - Scanlon, P. H.; Loftus, J.; Starita, C.; Stratton, I. M.
Abstract Aims To examine the relationship between visual acuity in each eye and Quality of Life (QoL) outcomes in people with diabetic macular oedema. Methods Cross sectional retrospective analysis of data collected at baseline in 289 people entered into a randomized clinical trial with diabetic macular oedema which investigated the safety and efficacy of a vascular endothelial growth factor inhibitor, pegaptanib sodium. At the baseline visit, visual acuity was measured through refraction and using retro‐illuminated modified Early Treatment Diabetic Retinopathy Study Log MAR charts, and patient health‐related QoL was determined using the European Quality of Life EQ–5D–3L and the Visual Functioning Questionnaire–25 (NEI–VFQ25). A regression analysis with QoL score from each vision‐related domain as the dependent variable was fitted using linear and quadratic terms of the better and worse eye, age, gender, adjusted for number of concurrent conditions, ethnicity and level of diabetes control. Results For all vision‐related QoL domains from NEI–VFQ25 and EQ–5D–3L except ocular pain, both visual acuity in the better‐seeing and the worse‐seeing eye gave a significant increase in correlation coefficient over that obtained from clinical and demographic data. The NEI–VFQ25 correlation was most closely associated with a weighted visual acuity measure of 0.75 in the better and 0.25 in the worse eye or 0.60 in the better and 0.40 in the worse eye. Conclusions We recommend that a weighted visual acuity measure from both eyes is considered in future diabetic macular oedema trials.